2013
DOI: 10.1021/ic401960x
|View full text |Cite
|
Sign up to set email alerts
|

Spin Crossover Meets Diarylethenes: Efficient Photoswitching of Magnetic Properties in Solution at Room Temperature

Abstract: A photoisomerizable diarylethene-derived ligand, phen*, has been successfully introduced into a spin-crossover iron(II) complex, [Fe(H2B(pz)2)2phen*] (1; pz =1-pyrazolyl). A ligand-based photocyclization (photocycloreversion) in 1 modifies the ligand field, which, in turn, results in a highly efficient paramagnetic high-spin → diamagnetic low-spin (low-spin → high-spin) transition at the coordinated Fe(II) ion. The reversible photoswitching of the spin states, and thus the associated magnetic properties, has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
146
1
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(166 citation statements)
references
References 72 publications
14
146
1
5
Order By: Relevance
“…Recently Khusniyarov et al have used a phenanthroline ligand functionalized by a photochromic diarylethene moiety in a bis(pyrazolyl)borate Fe(II) complex ( Figure 6). Under UV-irradiation, the open HS form is reversibly converted (about 40%) to a LS closed form [49,50]. In parallel, Oshio et al studied similar compounds and showed bidirectional spin-state switching by LIESST and reverse-LIESST in the solid state and in butyronitrile solution [51].…”
Section: Spin State Change By Ligand Field Strength Modulationmentioning
confidence: 99%
“…Recently Khusniyarov et al have used a phenanthroline ligand functionalized by a photochromic diarylethene moiety in a bis(pyrazolyl)borate Fe(II) complex ( Figure 6). Under UV-irradiation, the open HS form is reversibly converted (about 40%) to a LS closed form [49,50]. In parallel, Oshio et al studied similar compounds and showed bidirectional spin-state switching by LIESST and reverse-LIESST in the solid state and in butyronitrile solution [51].…”
Section: Spin State Change By Ligand Field Strength Modulationmentioning
confidence: 99%
“…An interesting recent access to trapped spin states relies on light-driven isomerization within the ligand sphere. Here the spin state is altered via variation of the ligand-field strength (light-driven ligand-induced spin change, LD-LISC [9,10]) or variation of the ligand-field symmetry (light-driven coordination-induced spin-state switching, LD-CISSS [11,12]). Most commonly, however, it is only at cryogenic temperatures,…”
Section: Introductionmentioning
confidence: 99%
“…For example, diarylethenes bearing thiophene moiety and six-membered pyridine unit exhibited good photochromism both in solution and in the crystalline phase by permitting the pyridine unit to participate in the photoinduced cyclization reaction [5][6][7]. What's more, the bearing of heteroatom of diarylethenes can dramatically change photochromism properties and expand multiple responsive switching systems [8,9]. Herein, we have designed and synthesized a new diarylethene bearing thiophene moiety and pyridine unit, namely 1-[2-methyl-5-(2-pyridyl-3thienyl]-2-[2-methyl-5-(4-bromomethylphenyl)-3-thienyl]perfluorocyclopentene.…”
Section: Introductionmentioning
confidence: 99%